STRATEGIC LEADERSHIP IN DIGITAL EDUCATION: TRANSFORMING SCHOOL MANAGEMENT IN THE AI ERA - Mohamad Kamil Salas; Masluhah Masluhah (CV. Lafadz Jaya, 2026)
The digital transformation of education triggered by the development of artificial intelligence demands fundamental changes in leadership practices within schools. This study aims to analyze the role of strategic leadership in managing and transforming school management in the AI ​​era through a literature review approach. The method used is a systematic literature review by reviewing various scientific sources in the form of reputable journals, academic books, and research reports related to strategic leadership, digital education, and the integration of AI in education management. The results of the study indicate that strategic leadership plays a crucial role in formulating a digital vision, developing a culture of innovation, and managing technology-based organizational change. Furthermore, school leaders are required to possess adaptive competencies, digital literacy, and data-driven decision-making skills to optimize the implementation of AI in the learning process and school administration. This study also found that the success of digital transformation is greatly influenced by collaboration between leaders, teachers, and other stakeholders, as well as adequate infrastructure and policy support. Thus, strategic leadership is key to creating a responsive, innovative, and sustainable school management system in the AI ​​era.